A Novel Small Vertical Axis Wind Turbine Using Delta-Wing Blades. Issue 4 (August 2014) - Ji, X. N.; Schlüter, J. U.
We present a novel Vertical Axis Wind Turbine (VAWT) that uses flat delta-wings instead of aerodynamically shaped blades with airfoil cross-sections. This choice lowers the manufacturing costs significantly. Furthermore, delta-wings have a good aerodynamic efficiency at low Reynolds-numbers compared to conventional blades. This is in particular an advantage, if delta-wings are used in small wind turbines. We have performed wind tunnel measurements at low tip-speed ratio and showed that the power output of the delta-wing turbine is higher than that of a conventional straight-bladed VAWT.